Factors Affecting Manufacturing Exports - Euis Eti Sumiyati (Journal of Economics, Business, and Accountancy Ventura, 2020)
This study aims to determine the factors that influence manufacturing exports inIndonesia. This study uses time-series data with 40 data observations starting fromthe 1st quarter of 2010 to the 4th quarter of 2019. This study's analysis method is theÂ vector error correction model (VECM), which can dynamically describe the shortterm and long-term effects. Export determinants to be examined are inflation, theÂ rupiah exchange rate, Gross Domestic Product (GDP), and Foreign DirectInvestment (FDI). This study indicates that inflation at lag 1 harms manufacturedexports both in the short and long term. Furthermore, GDP has a positive effect onmanufacturing exports in the short run at lag 1 and lag 2, while in the long run, GDPhas a positive effect only on lag 1. Meanwhile, the exchange rate and FDI factors didnot affect manufactured exports, both in the short and long term. This study impliesthat inflation and GDP are essential factors in designing policies to increase exportsin Indonesia, including exports of manufactured products.